Revealing the Future of Pharmacovigilance in Precision Pharmaceutical Monitoring - Mittal, Vishnu; Sharma, Anjali (Current Drug Safety, 2025)
The growing popularity of personalized medicine presents new hazards and difficulties for pharmacovigilance. This implies that it needs to modify its current approach. This research examines how drug safety monitoring for certain medications evolves over time. We briefly discuss the connection between meticulous pharmacovigilance procedures and adaptable treatment approaches. We describe how pharmacogenetics may be used to make drugs safer and how genetic testing may be used to forecast a drug's potential side effects. With an emphasis on post-marketing monitoring in phase IV, we address shortcomings of research on pre-marketing and the need for a comprehensive strategy for medication safety. The significance of pharmacogenetics in reducing risk before exposure and the need to reconsider pharmacoepidemiological techniques for monitoring outcomes after exposure are discussed in the study. We emphasize the significance of including genetic patient-specific profiles in publications related to tailored therapy and the use of state-of-the-art computer techniques for data processing. We also discuss privacy, ethical, and data security issues that arise with precision medicine, emphasizing the consequences for patient consent and data management.
Keywords: drug safety